Evolutionary Conservation of the Orchid MYB Transcription Factors DIV, RAD, and DRIF - Valoroso, Maria Carmen; Sobral, Rómulo; Saccone, Giuseppe; Salvemini, Marco; Costa, Maria Manuela Ribeiro; Aceto, Serena (Frontiers in Plant Science, 2019)
The MYB transcription factors DIVARICATA (DIV), DIV-and-RAD-Interacting-Factor (DRIF) and the small interfering peptide RADIALIS (RAD) can interact forming a regulatory module that controls different plant developmental processes. In the snapdragon Antirrhinum majus, this module, together with the TCP transcription factor CYCLOIDEA (CYC), is responsible for the establishment of floral dorsoventral asymmetry. The spatial gene expression pattern of the OitDIV, OitDRIF and OitRAD homologs of Orchis italica, an orchid with zygomorphic flowers, has suggested a possible conserved role of these genes in bilateral symmetry of the orchid flower. Here, we have identified four DRIF genes of orchids and have reconstructed their genomic organization and evolution. In addition, we found snapdragon transcriptional cis-regulatory elements of DIV and RAD loci generally conserved within the corresponding orchid orthologues. We have tested the biochemical interactions among OitDIV, OitDRIF1 and OitRAD of O. italica, showing that OitDRIF1 can interact both with OitDIV and OitRAD, whereas OitDIV and OitRAD do not directly interact, as in A. majus. The analysis of the quantitative expression profile of these MYB genes revealed that in zygomorphic orchid flowers the DIV, DRIF1 and RAD transcripts are present at higher levels in the lip than in lateral inner tepals, whereas in peloric orchid flowers they show similar expression levels. These results indicate that MYB transcription factors could have a role in shaping zygomorphy of the orchid flower, potentially enriching the underlying orchid developmental code.